Seasonal Inventory Decisions (Single-Period Inventory Models) - Rudy Santosa Sudirga (Universitas Bunda Mulia, 2015)
One of the dilemmas facing many retailers is how to handle seasonal goods, such as sarung dress or batik dress, biscuits and syrups during Idul Fitri celebration. Often they cannot be sold at full markup next year because of changes in styles, and expiry dates for foods and beverages. Furthermore, the lead time can be longer than the selling season, allowing no second chance to rush through another order to cover unexpectedly high demand. At the end of the period the product has either sold out or there is a surplus of unsold items to sell for a salvage value. The single-period inventory models are used in situations involving seasonal or perishable items that cannot be carried in inventory and sold in future periods.This type of situation is often called the newsboy problem. If the newspaper seller does not buy enough newspapers to resell on the street corner, sales opportunities are lost. If the seller buys too many newspapers, the overage cannot be sold because nobody wants yesterday’s newspaper.At this opportunity, we will use the single-period inventory models decisions to create an optimal order quantity decision with the highest expected payoff. We will be able to use this decision process for all such items over many selling seasons to maximize profits.However, it is not a foolproof, and it can result in an occasional bad outcome. It will depend on the situation, if the probability of demand follows the demand probability planning, then you will be able to get the best decision to prepare and execute an order.Kata kunci:Seasonal Inventory, Single-Period Inventory Models, Probability of Demand.